(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was carried out to determine stakeholder’s perception of adequacy of technology education programme in Nigerian Universities for acquisition of requisite employable skills by students. Three research questions guided the study and two null hypotheseswere tested at 0.05 level of significance. Descriptive survey research design was used for the study. A validated questionnaire with reliability coefficient of 0.73 was used for data collection. The population was made up of 227 technology education students, 57 trainers and 33 employers of technology education graduates from the three zones that make up northern Nigeria. Both multi-stage and purposive sampling techniques were used resulting to a sample size of 188 respondents (128 students, 37 trainers and 33 employers, drawn from three universities. Mean and standard Deviation were used to answer the research questions using a benchmark of 2.50 as an index for agreement and to determine the homogeneity or otherwise of the respondents. z-Test was used to test the two null hypotheses. The findings showed that the technology education programme in Nigerian universitiesis adequate for equipping students with theappropriategeneric skillsregardless of their stress areas. The programme wasfound not adequate for equipping the students with the skills needed for industrial work and self- reliance among others. Based on the findings the researcher recommended among others that curriculum planners should integrate more professional technology education courses on emerging problems in technology education into the programme to complement the employability skills.